Strategic network expansion of urban rapid transit systems: A bi‐objective programming model. (29th November 2018) - Wei, Yi; Jin, Jian Gang; Yang, Jingfeng; Lu, Linjun
Abstract: With the development of urbanization and the extension of city boundaries, the expansion of rapid transit systems based on the existing lines becomes an essential issue in urban transportation systems. In this study, the network expansion problem is formulated as a bi‐objective programming model to minimize the construction cost and maximize the total travel demand covered by the newly introduced transit lines. To solve the bi‐objective mixed‐integer linear program, an approach called minimum distance to the utopia point is applied. Thus, the specific trade‐off is suggested to the decision makers instead of a series of optimal solutions. A real‐world case study based on the metro network in Wuxi, China, is conducted, and the results demonstrate the effectiveness and efficiency of the proposed model and solution method. It is found that the utopia method can not only provide a reasonable connecting pattern of the network expansion problem but also identify the corridors with high priority under the limited budget condition.